Youth’s engagement and perceptions of disposable e-cigarettes: a UK focus group study - Shona Hilton; Anne Marie MacKintosh; Allison Ford; Marissa J Smith (BMJ Open, 2023)
Objectives Evidence suggests that use of flavoured disposable electronic cigarettes (e-cigarettes) is increasing. Considering the growing popularity and rapid evolution of e-cigarettes, we explored youth’s perceptions and engagement with disposable e-cigarettes.Design Twenty focus groups were conducted between March and May 2022, with 82 youths aged 11–16 living in the Central belt of Scotland.Methods Youths were asked about smoking and vaping behaviours and disposable e-cigarettes and were shown vaping-related images and videos from social media which were used to stimulate discussion about different messages, presentations and contextual features. Transcripts were imported into NVivo V.12, coded thematically, and analysed.Results Youths described disposable e-cigarettes as ‘cool’, ‘fashionable’ and enticing and viewed as a modern lifestyle ‘accessory’. Tank models were perceived as being used by older adults. Youths stated that disposable e-cigarettes were designed in a way to target youths and the brightly coloured devices and range of flavourings encouraged youths to want to try the products, particularly sweet flavourings. Participants perceived e-cigarettes to be less harmful compared with combustible cigarettes but noted the uncertainty of ingredients in disposable e-cigarettes.Conclusions Youths distinguish between e-cigarettes with varying characteristics and social perceptions of users. These findings provide evidence that disposable e-cigarettes are attractive to youths. Future research is needed to understand the factors that contribute to youth perceptions of disposable e-cigarettes. Policymakers should work together to design and implement policies and strategies to prevent youth uptake of vaping.